PENERAPAN BUSINESS INTELIGENCE UNTUK MENGANALISIS DATA PENJUALAN MENGGUNAKAN POWER BI - Annas Purnama; I Nyoman Yudi Anggara Wijaya; Ida Bagus Kresna Sudiatmika (Jurnal Informatika Teknologi dan Sains, 2022)
Warung Blaster and Warung Bhineka Sanur are restaurants that combine Asian, Italian and Western food. In processing sales data, Warung Blaster and Warung Bhineka Muda Sanur still perform manual processes in Microsoft Excel. So that the data can be processed into valuable information, a Business intelligence (BI) software is needed that can visualize the data so that it can display information about sales data. The development of a Business Intelligence system in processing dashboard system-based data using Microsoft Power BI has resulted in good information in the form of graphic visualization. Warung Blaster and Warung Bhineka Muda Sanur are able to apply Business Intelligence based on a dashboard system to make it easier to generate sales reports and can help analyze a problem and determine the performance of each business.